2019
DOI: 10.4028/www.scientific.net/ssp.290.323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu Doped in MgO on Nanostructures and their Band Gap Energies

Abstract: Doping of the materials with other metals or transition metals will modify the properties of the nanomaterials. In this work, MgO and Cu doped MgO which are Mg0.95Cu0.05O and Mg0.90Cu0.10O nanomaterials are synthesized using a self-propagating combustion method. The samples are annealed at 900 °C for 24 hours. The phase and purity of the synthesized samples are studied using X-Ray Diffraction (XRD) and the result revealed that the samples are pure and single phase. The morphology and crystallite size of the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This decrease could be the result of Zn inducing various defects, like oxygen vacancies, into the MgO lattice. As a results, Zn doping causes the MgO bands to enter new energy levels and decreases the band gap of the MgO thin lms [19,23]. We observed also that when the band gap is decreased, inversely proportional to the Urbach energy.…”
Section: Optical Propertiesmentioning
confidence: 50%
“…This decrease could be the result of Zn inducing various defects, like oxygen vacancies, into the MgO lattice. As a results, Zn doping causes the MgO bands to enter new energy levels and decreases the band gap of the MgO thin lms [19,23]. We observed also that when the band gap is decreased, inversely proportional to the Urbach energy.…”
Section: Optical Propertiesmentioning
confidence: 50%
“…Different methods have been reported for the synthesis of metal ion doped MgO NPs. For example, synthesis of Ag-doped MgO NPs via successive ionic layer adsorption and reaction (SILAR) [9], Ce-doped MgO NPs by sol-gel [10], and Cu-doped MgO NPs by self-propagating combustion [11]. Parvizi and coworkers observed that Zn doping decreased the band gap energy and increased the optical activity of MgO [12].…”
Section: Introductionmentioning
confidence: 99%
“…These new compound will exhibit different characteristics than their parent material that will be useful for future applications [6,7]. Previously, doped MgO nanostructures has been reported with various dopant elements such as Cu, Zn, Ca, etc and results has been proved that the band gap change when it undergo doping [8][9][10][11]. MgO doped with tunable band gap will become as a promising material for potential semiconductor applications.…”
Section: Introductionmentioning
confidence: 99%